2015
DOI: 10.1016/j.jsps.2014.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Sampling time and indications appropriateness for therapeutically monitored drugs at a teaching university hospital in Oman

Abstract: TDM service is much less than optimal in SQUH. A lot of effort needs to be carried out to improve TDM use in the developing countries as adjusting the doses on results that are based on wrong sampling time might expose patients to toxicity or therapeutic failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
7
5
0
Order By: Relevance
“…Our findings are consistent with the few available vancomycin TDM audits in the MENA region and elsewhere . Al‐Zaabi and colleagues reported two studies in Oman that were conducted at two different time points .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our findings are consistent with the few available vancomycin TDM audits in the MENA region and elsewhere . Al‐Zaabi and colleagues reported two studies in Oman that were conducted at two different time points .…”
Section: Discussionsupporting
confidence: 90%
“…Most vancomycin TDM requests were appropriately indicated but inappropriately timed . Moreover, dosage adjustments were applied in many incorrectly sampled specimens, suggesting false dosing and inappropriate interpretation of TDM results . Consistent with our findings, higher tendency to apply dosage adjustments in response to supratherapeutic concentrations rather than subtherapeutic concentrations has been reported .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The purpose of TDM is to individualise the therapeutic regimen of the patient to gain optimal benefit with the lowest toxicity. Research has shown blood samples for TDM purposes are not always taken correctly and protocols do not exist, or are not always followed,2 which can lead to incorrect dosing regimens and waste of time and resources, especially in developing countries 2…”
Section: Introductionmentioning
confidence: 99%